Factors affecting consumers' preferences for electric vehicle: A Korean case. (December 2021) - Jung, Jihyeok; Yeo, Sangmin; Lee, Yeonjeong; Moon, Saedaseul; Lee, Deok-Joo
Abstract: This paper presents a stated preference study of electric vehicles (EVs) in the Korean automobile market based on the survey data, which was conducted in February 2018 in Korea. The purpose of this study is to analyze empirically the factors related to the consumers' attitudes toward environmental issues and vehicle attributes that significantly affect the EV preferences of potential Korean consumers. We categorized the survey into two parts: discrete car choice questionnaire and consumers' attitude questionnaire. A total of 1251 respondents were asked to choose their preferred vehicle type between internal combustion engine vehicle and electric vehicle in discrete car choice questionnaire. Their attitude toward environmental issues and vehicle attributes were revealed in the attitude questionnaire. A hybrid choice model is used to jointly integrate Korean consumers' attitudes and their choice decisions. As a result, we figured out that consumers who favor EVs are sensitive to environmental pollution issues, especially in vehicle pollution, and place high importance on the future value of automobiles and less importance on vehicle aesthetics when purchasing a car. Also, economic factors such as purchase price and charger subsidies, and charging infrastructure are necessary for successful EV adoption in Korea, with the possibility of a positive externality effect of using EVs.